TATA LAKSANA BRAKHITERAPI CO-60 TEKNIK INTRAKAVITER LENGKAP PADA KASUS KANKER SERVIKS - Nugroho Yudho Susilo; Rini Indrati; Nanang Sulaksono (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background: Brachytherapy is a radiation treatment by bringing radiation sources closer to the primary tumor which aims to provide additional therapeutic doses (booster) after external radiation administration so that the optimal dose will be achieved. In general brachytherapy uses closed radioactive sources namely Radium, Cobalt-60, Cesium- 137, and Iridium-192.Intracaviter technique is a type of brachytherapy technique in which the radiation source is placed in a hilt and inserted into a body organ that contains a tumor. to obtain the optimal dose distribution. Methods: The type of research used is qualitative research with a case study approach. The study was conducted by observation, documentation and interviews. The subjects of this study were one radiation oncology specialist, one medical physicist, one radiotherapy radiographer, and one radiotherapy nurse at the Radiotherapy Installation of Dr. Moewardi Hospital. Stages The data analysis in this study used the data analysis method which was done descriptively using interactive models. Results: The results showed that the management of radiotherapy in cervical cancer patients at Radiotherapy Hospital Dr. The procedure consists of several procedures, namely the control of a specialist oncologist of radiation after external radiation, supporting examinations (check vital signs, laboratory, ECG, and chest X-ray), undergoing hospitalization a day before irradiation of brachytherapy, spinal anesthesia before applying the applicator, applying an applicator, simulating the position of the applicator with AP and Lateral x-ray projections, calculating the dose (2 x 850 cGy) and irradiation time in the TPS (Treatment Planning System) room based on the Manchester system dose distribution, and irradiation in the brachytherapy room. Conclusion: Management of brachytherapy consists of several procedures, namely the control of radiation oncology specialists, supporting examinations, undergoing hospitalization the day before exposure, spinal anesthesia, applying applicators, simulating applicator positions, calculating doses and exposure time in the TPS (Treatment Planning System) ) based on the Manchester system dose distribution, and carried out irradiation in the brachytherapy room. The reason for using three Co-60 sources in one fraction of brachytherapy irradiation is because it can shorten the irradiation time and minimize the time error arising when the source moves. Evaluation of Co-60 brachytherapy patients in cervical cancer cases can be estimated in the form of tumor response, in patients experiencing total response and not experiencing side effects such as cystitis or progitis.